Novel Wear-Resistant Mechanism Induced by MUPZs via RRA Process in Microalloyed High Manganese Steel - Rui Wang; Xiaomin Huang; Wen Zhang; Hao Fu; Xin Chen; Zulai Li; Quan Shan (Metals, 2023)
Microalloying and heat treatment have been regarded as an efficient way to get higher wear resistance in high manganese steel, and multiscale precipitates can be obtained randomly by the aging process; however, most of the previous work on heat treatment was more concerned with peak aging time and not the synergistic mechanism of different sized precipitates. Here, we propose a novel wear-resistant mechanism by multiscale precipitates regulated via a retrogression and re-aging (RRA) process. Micron, submicron, and nano precipitates are obtained by the RRA process and jointly form micro-scale ultrafine precipitation zones (MUPZs), which can protect the matrix surface and reduce the abrasive embedded probability, thus ameliorating the micro-cutting and micro-plowing mechanisms. This novel wear-resistant mechanism induced by MUPZs shows better effect under high impact energy due to sufficient work hardening caused by the interaction between dislocations and multi-scale precipitates in MUPZs. This work was investigated using SEM, EDS, and TEM, combined with mechanical properties and impact abrasive wear tests.